(untitled) (Research, Society and Development, 2020)
Objective: Analyze how permanent health education has been used as a strategy for qualifying the teams of urgent and emergency services. Method: Integrative Literature Review, carried out through five databases and a digital library, having as inclusion criteria: types of study, language and time frame. The final sample consisted of 11 studies. Results: As a result of the evidence synthesis, two thematic categories emerged: "The relevance of Permanent Education as a strategy for professional qualification in urgent and emergency services" and "Methods used in the implementation of Permanent Education in urgent and emergency services". Conclusion: The integrative review became effective, pointing out the relevance of permanent education for the professional qualification and performance, allowing us to realize the importance of this being more stimulated and incorporated into urgent and emergency services, and emphasizing that this will provide skills and better efficiency in customer service. It was possible to observe that the various methods that are being used aiming at the implementation of this educational practice, highlighting the use of the technology associated with it. The evidence obtained can be useful for discussions on the subject and for future research.